(untitled) (IJM: Journal of Multidisiplinary, 2025)
The concept of humanity in Islam holds a central position in designing a holistic and meaningful education system. Humans are viewed as beings with a natural disposition (fitrah), possessing intellectual and spiritual potential, and entrusted with the role of caliph on earth. This perspective provides both philosophical and practical frameworks for the development of Islamic education that not only aims to cultivate intelligence but also to shape noble character and morals. Islamic education, grounded in the principle of tawhid (the oneness of God), sees the entire learning process as a means to draw closer to Allah SWT and to develop a balanced individual between worldly life and the hereafter. This article aims to explore the essence of humanity according to Islam and how this concept serves as the foundation for forming a relevant and transformative Islamic education system. Using a qualitative literature review approach, this study concludes that integrating the values of tawhid, amanah (trustworthiness), and human fitrah into the curriculum and learning processes can produce a civilized generation ready to face contemporary challenges without losing their spiritual identity.